Pengaruh Penggunaan Pertanyaan Pemantik Terhadap Peningkatan Hasil Belajar Siswa Kelas II Sekolah Dasar Pada Pembelajaran PAI - Wanda Juliani Saputri J; Helen Sabera Adib; Emilia Fitri (PAI RAFAH, 2025)
This study aims to determine the use of lighter questions, how to improve the learning outcomes of grade II students, and the effect of using lighter questions on the learning outcomes of grade II students in learning Islamic Religious Education at SD IBA Palembang. This study used quantitative approach with experimental research method and One Group Pretest-Posttest Design design. The research population was all grade II students as many as 65 students, with the technique of taking saturated samples. The data collection techniques used were observation, tests, and documentation. Data analysis was carried out with descriptive statistics and inferential statistics, using normality tests, and hypothesis tests. The results showed that the use of lighter questions was carried out with the stages of greetings, prayers, and delivery of learning objectives, presentation of three lighter questions in the introduction phase for 15 minutes, drawing conclusions, and prayers. There was an increase in learning outcomes of grade II students by 17% after the application of sparking questions. The analysis shows that there is a significant influence between the use of sparking questions and the learning outcomes of grade II students, seen from the value of r count of 12.098 and r table of 1.998. Therefore the value of r count> r table, so it can be concluded that Ha is accepted and H0 is rejected.